Comanche - Bird, F. A. (Minneapolis, Minnesota : Checkerboard Library, 2022)
This book introduces young readers to the Comanche people, their traditional ways of life, including social structure, homes, food, art, clothing and more, their contact with Europeans, and how the Comanche are keeping their culture alive today.
Homelands -- Society -- Homes -- Food -- Clothing -- Crafts -- Family -- Children -- Traditions -- War -- Contact with Europeans -- Quanah Parker -- The Comanche today.
Includes index.
4.4
3-6
770L
Keywords: Comanche Indians -- Juvenile literature; Indigenous peoples -- Social life and customs -- Juvenile literature; Ethnology -- Juvenile literature; Comanche Indians; Indigenous peoples -- Social life and customs; Ethnology; Indians of North America -- Juvenile literature